The Relationship between Natriuretic Peptide Precursor a Gene T2238C Polymorphism and Hypertension: A Meta-Analysis - Wenquan Niu (International Journal of Hypertension)
Single studies attempting to associate ANP gene T2238C (rs5065) polymorphism with hypertension have so far reported inconclusive results. We therefore aimed to evaluate this association via a meta-analysis. Data on 7 studies with a total of 4068 subjects were available and analyzed using the random-effects model with assessment of heterogeneity and publication bias. Overall comparison of 2238C with 2238T yielded a 23% reduced, albeit nonsignificant, risk for hypertension (95% CI: 0.38–1.59; P=.485), while accompanying significant heterogeneity (I2=88.3%) and publication bias (P=.051). Subgroup analysis by study design demonstrated opposite associations between population-based (OR=0.33; 95% CI: 0.13–0.80; P=.015) and hospital-based studies (OR=1.15; 95% CI: 0.79–1.68; P=.454). Further meta-regression analysis exclusively indicated the significant influence of study design (P=.042) on heterogeneity. Taken together, these findings support the notion that carriers of 2238C allele were at moderate decreased risk of developing hypertension, whereas study design was identified as a potentially significant source of between-study heterogeneity.